Safety and Efficacy of HIV Hyperimmune Globulin (HIVIGLOB) for Prevention of Mother-to-Child HIV Transmission in HIV-1 infected Pregnant Women and their Infants in Kampala, Uganda (HIVIGLOB/NVP STUDY) - Makumbi, Carolyne Onyango; Omer, Saad B.; Mubiru, Michael; Moulton, Lawrence H.; Nakabiito, Clemensia; Musoke, Philippa; Mmiro, Francis; Zwerski, Sheryl; Wigzell, Hans; Falksveden, Lars; Wahren, Britta; Antelman, Gretchen; et al. (Journal of acquired immune deficiency syndromes, 2011)
This phase III randomized clinical trial compared single dose nevirapine (sdNVP) plus HIV immunoglobulin (HIVIGLOB) to sdNVP alone for preventing maternal-to-child transmission (PMTCT) of HIV.Primary objectives were to determine rates of HIV infection among infants, and to assess the safety of HIVIGLOB in combination with sdNVP in HIV-infected Ugandan pregnant women and their infants.Mother-infant pairs were randomized to receive 200mg of NVP to women in labor and 2mg/kg NVP to newborns within 72 hours after birth (sdNVP arm) or to receive sdNVP plus a single intravenous 240ml dose of HIVIGLOB given to women at 36-38 weeks gestation and a single intravenous 24ml dose to newborns within 18 hours of birth (HIVIGLOB/sdNVP arm). Risk of HIV infection was determined using Kaplan-Meier and risk ratio estimates at birth, 2, 6, 14 weeks, 6 and 12 months of age. Intent-to-treat analysis included 198 HIVIGLOB/sdNVP and 294 sdNVP mother-infant pairs. At 6 months of age, the primary endpoint, there was no statistically significant difference in HIV transmission in the HIVIGLOB/sdNVP arm versus the sdNVP arm (18.7% vs.15.0%; RR =1.240 [95% CI: 0.833-1.846]; p= 0.290). Similarly, the proportion of serious adverse events in the HIVIGLOB/sdNVP and sdNVP arms, respectively for mothers (18.9% vs. 19.3%; p= 0.91) and infants (62.6% vs. 59.5%; p=0.51), were not significantly different.Giving mother-infant pairs an infusion of peripartum HIV hyperimmunoglobulin in addition to sdNVP for PMTCT was as safe as sdNVP alone, but was no more effective than sdNVP alone in preventing HIV transmission.
Keywords: HIV, HIVIGLOB, sdNVP, breastfeeding, PMTCT, Uganda